Single‐stage revision of MRSA orthopedic device‐related infection in sheep with an antibiotic‐loaded hydrogel. Issue 2 (23rd December 2020) - Foster, Andrew L.; Boot, Willemijn; Stenger, Valentina; D'Este, Matteo; Jaiprakash, Anjali; Eglin, David; Zeiter, Stephan; Richards, Robert G.; Moriarty, Thomas F.
Abstract: Local antimicrobial therapy is an integral aspect of treating orthopedic device‐related infection (ODRI), which is conventionally administered via polymethyl‐methacrylate (PMMA) bone cement. PMMA, however, is limited by a suboptimal antibiotic release profile and a lack of biodegradability. In this study, we compare the efficacy of PMMA versus an antibiotic‐loaded hydrogel in a single‐stage revision for chronic methicillin‐resistant Staphylococcus aureus (MRSA) ODRI in sheep. Antibiofilm activity of the antibiotic combination (gentamicin and vancomycin) was determined in vitro. Swiss alpine sheep underwent a single‐stage revision of a tibial intramedullary nail with MRSA infection. Local gentamicin and vancomycin therapy was delivered via hydrogel or PMMA ( n = 5 per group), in conjunction with systemic antibiotic therapy. In vivo observations included: local antibiotic tissue concentration, renal and liver function tests, and quantitative microbiology on tissues and hardware post‐mortem. There was a nonsignificant reduction in biofilm with an increasing antibiotic concentration in vitro ( p = 0.12), confirming the antibiotic tolerance of the MRSA biofilm. In the in vivo study, four out of five sheep from each treatment group were culture‐negative. Antibiotic delivery via hydrogel resulted in 10–100 times greater local concentrations for the first 2–3 days compared with PMMA and were comparable thereafter. Systemic concentrations of gentamicin were minimal or undetectable in both groups, while renal and liver function tests were within normal limits. This study shows that a single‐stage revision with hydrogel or PMMA is equally effective, although the hydrogel offers certain practical benefits over PMMA, which make it an attractive proposition for clinical use.